Effect of the polyimide structure and ZnO concentration on the morphology and characteristics of polyimide/ZnO nanohybrid films - Hsu, SC; Whang, WT; Hung, CH; Chiang, PC; Hsiao, KN (My University, 2005)
A series of polyimide/ZnO nanohybrid films with different ZnO content were prepared from a rigid pyromellitic dianhydride-4,4'-diaminodiphenyl ether (PMDA-ODA) polyimide (PI) and a flexible 3,3,4,4-benzophenonetetracarboxylic acid dianhydride-4,4'-diaminodiphenyl ether (BTDA-ODA) PI with ZnO nanoparticles (3-4 nm). Fourier-transform infrared (FT-IR) and X-ray photoelectron spectroscopy (XPS) depict that the ZnO nanoparticles function as a physical cross-linking agent with PI through hydrogen bonding between the OH on the ZnO nanoparticles and the C=O of the imide groups. ZnO nanoparticles in the rigid PMDA-ODA matrix cause a larger percentage decrease in the coefficient of linear thermal expansion (CTE) than in the flexible BTDA-ODA matrix. The BTDA-ODA/ZnO hybrid films have two transition peaks in dynamic mechanical tan curves, but PMDA-ODA/ZnO hybrid films only have one transition peak. Thermogravimetric analysis reveals that ZnO decreases the thermal degradation temperature (T-d) in both hybrid films, but less so in PMDA-ODA/ZnO films. Trans-mission electron microscopy (TEM) images reveal that the rigid matrix induces larger particle size (30-40 nm) compared to the flexible matrix (10-15 nm).
Keywords: nanocomposites; polyimides; structure-property relations; thermal properties; ZnO